IMPLEMENTATION OF THE JEAN MEEUS ALGORITHM IN CALCULATING NEW MOON AND FULL MOON DATA - Venia, Susan (Fakultas Syari'ah dan Hukum UIN Walisongo, 2024)
This research aims to determine the application of Jean Meeus' algorithm in calculating new moon and full moon data. This is a qualitative study using a library approach. The primary source is the book